Numerical Solution of Hydromagnetic Chemically Reacting and Radiating Casson Fluid Flow Past a Permeable Vertical Stretching Surface (International Journal of Food and Nutritional Sciences, 2019)
In this investigation, we explore the combined effects of a magnetic field, thermal radiation,buoyancy force, viscous dissipation, and chemical reaction on the flow of a Casson fluid overa permeable stretching surface. The nonlinear model equations are formulated andtransformed into a set of ordinary differential equations (ODEs).